The effect of bio-banding on technical and tactical indicators of talent identification in academy soccer players. Issue 3 (3rd July 2022) - Towlson, Christopher; MacMaster, Calum; Gonçalves, Bruno; Sampaio, Jaime; Toner, John; MacFarlane, Niall; Barrett, Steve; Hamilton, Ally; Jack, Rory; Hunter, Frances; Stringer, Amy; Myers, Tony; et al.
ABSTRACT: Aim: The aim of this study was to examine the effect of bio-banding on technical and tactical markers of talent identification in 11- to 14-year-old academy soccer players. Methods: Using a repeated measures design, 92 players were bio-banded using percentage of estimated adult stature attainment (week 1), maturity-offset (week 2) and a mixed-maturity method (week 3). All players contested five maturity (mis)matched small-sided games with technical and tactical variables measured. Data were analysed using a series of Bayesian hierarchical models, fitted with different response distributions and different random and fixed effect structures. Results: Despite differences during maturity-matched bio-banding for post-peak height velocity players, very few tactical differences were evident during the remaining maturity-matched and mis-matched fixtures for both banding methods. In fact, the results showed no consistent differences across both banding methods for practitioner and video analysis-derived technical performance characteristics during maturity matched and mis-matched fixtures. Both bio-banding methods explained similar levels of variance across the measured variables. Conclusion: Maturity-matched bio-banding had some effect on both technical and tactical characteristics of players during maturity-matched bio-banded formats. That said, this trend remained during maturity mis-matched bio-banded formats which restricts the conclusions that can be made regarding the effectiveness of bio-banding to manipulate technical and tactical measures in academy soccer players.